Reminiscence Therapy Improves the Quality of Life of the Elderly - Caecilia Titin Retnani; Junaiti Sahar; Wiwin Wiarsi (Sekolah Tinggi Ilmu Kesehatan Ngesti Waluyo, 2021)
Elderly in 2050 is predicted to increase to 1.5 billion. The addition of elderly number increases the incident of dementia. In addition, chronic diseases in the elderly are increasing. Chronic diseases have an impact on the quality of life of the elderly. Various non-pharmacological therapies are used to overcome these problems. Reminiscence therapy is proven to be effective in overcoming various problems of the elderly such as sleep disorders, depression, anxiety and quality of life the elderly. The purpose of this study is to provide an explanation of benefits of reminiscence therapy in the elderly. The research design was a literature review. Articles were searched using Clinical key, Pro quest, Sage, Science direct, and Wiley’s online library database year 2016-2021. The articles were extracted by looking at the duplication, title, abstract and full text so that it got 10 articles that were reviewed. The risk of bias in the article was reviewed using the JBI Checklist 2017. The result of several articles on reminiscence therapy showed a significant positive effect on quality of life, quality of sleep, reduced depressive symptoms, increased adaptation and coping to stress. As a conclusion, reminiscence therapy can be useful for improving the quality of life of the elderly.